Incentive structures as a capacity development strategy in public service delivery a literature review and annotated bibliography on the role of incentives for civil servants within capacity development policies - Ulleberg, Inger; Unesco. International Institute for Educational Planning (Paris UNESCO, International Institute for Educational Planning, 2009)
"Incentive structures play a crucial role when it comes to capacity development by motivating individuals and targeting organizational performance. Practitioners and academics have recently given more and more attention to incentives issues -- presented by a number of authors as the missing link in development. This literature review takes a closer look at how incentives are linked to motivation, performance and capacity development. The interplay between incentives and training is equally addressed. Chapter 2 of the review presents a typology of incentives, the different levels of analysis, and more general frameworks linked to capacity development. This publication emphasizes the distinction between financial and non financial incentives that target merit and accountability, and the importance of organizational culture. While recent literature draws the conclusion that incentives matter, incentive schemes do not always contribute to improved public performance, and may even represent an obstacle to capacity development.Chapter 3 attempts to identify the reasons linked to the failure of incentives in particular, and of public sector reform in general, including civil service reform. The limited impact of many incentives schemes is linked to competing disincentives leading to capacity erosion, such as sustained low wage levels, lack of transparency in recruitment or promotion based on political affiliation. The lack of knowledge about efficient use of non-financial incentives and human resources management tools, and the distorting effects of donor presence, are additional reasons for failure. When it comes to public sector reform, political will, existing capacity level, as well as the scope and sequencing of reform are crucial elements. Chapter 4 presents several relatively successful approaches to incentives. A number of these initiatives target not only performance, but accountability, team spirit or other organizational 'intangibles' that may have a positive impact on performance in the long run. Finally, Chapter 5 presents an overview of the general recommendations formulated by international agencies and various authors. An annotated bibliography follows, on which the literature review is based."--www.iiiep.unesco.org.
1. Rationale -- 2. Frameworks and types of incentives -- 3. Changes and challenges -- 4. Reforms and successes -- 5. Policy suggestions -- 6. The impact of incentives within the civil service on capacity development in education.
Keywords: Incentive awards; Incentives in industry; Civil service -- Labor productivity -- Developing countries; Employee motivation